Antifungal Susceptibility Testing of Pathogenic Aeromycoflora Isolated from Kathmandu - Shakya, Manju Shree; Shrestha, Anima; Shrestha, Gita Rajbhandari (Tribhuvan University Journal of Microbiology, 2021)
Objective: To identify the predominant pathogenic aeromycoflora present in dense areas of Kathmandu, and perform their antifungal susceptibility test. Methods: Aeromycoflora were isolated by the Gravity Plate method and identified by observing colony morphology and microscopic methods. For pathogenic mycoflora, MIC test was carried out following “Reference Method for Broth Dilution Antifungal Susceptibility Testing of Filamentous Fungi; Approved Standard. NCCLS document M38-A”. The antifungal agents used were Cotrimazole, Fluconazole, Ketoconazole, Itraconazole and Terbinafine available at pharmaceutical companies of Nepal during study period. Results: Penicillium spp (43.8%) was found to be the most predominant aeromycoflora followed by Cladosporium spp (35.5%), and pathogenic Aspergillus species (21.4%). Among Aspergillus species, Aspergillus niger (71.7%) was predominant, followed by A. flavus (17.1%) and A. fumigatus (11.1%). A. fumigatus and A. flavus were found to be most sensitive towards Itraconazole (MIC range – <0.0625 - 1μg/ml) while A. niger to Ketoconazole (MIC- 0.0625 - >32μg/ml). Conclusion: The finding of this study helped to identify the potent antifungal drugs available against the pathogenic aeromycoflora.